Measles vaccination policies in Europe: better performance at lower costs? - Antje Gottberg (2008)
WHO has targeted measles for eradication in the European region by 2007. Some countries have already met this target whereas others are still far from it. Comparative data on the different vaccination policies which determine success or failure of measles control programmes are scarce. In which way are the costs of vaccination influenced by the vaccination procedures in different countries? Four European countries (SF, D, NL, UK) were compared in terms of strategy and outcome of measles control. A set of variables was collected to describe the different vaccination policies as precisely as possible. The prices of MMR vaccines as well as other vaccination costs were evaluated for each of these countries and the respective outcomes were compared.